Seroprevalence to and influence of exposure to bovine reproductive disease causative agents on pregnancy and preweaning calf survival of elk (Artiodactyla: Cervidae) - Bender, Louis C.; Rosas-Rosas, Octavio C. (Instituto de Ecología, A.C., 2018)
Success of recent introductions of elk (Cervus elaphus Linnaeus, 1758) in Mexico partly depends upon elk livestock interactions and conflicts. Disease can impact reproduction of elk and cattle, but is seldom considered in wild ruminants when reproductive output declines. We surveyed serological exposure of elk to causative agents in a bovine abortion profile (i.e., agents of brucellosis, leptospirosis, infectious bovine rhinotracheitis (IBR), bovine viral diarrhea, and neosporosis), as these diseases can negatively affect reproduction of cattle and elk, which frequently co-occur. We determined seroprevalence of exposure to these agents and used hierarchical logistic regression to model both pregnancy and lactation status (a surrogate for calf survival to weaning) as a function of population and exposure to disease causative agents. Tested elk populations were exposed to 2–4 of the agents except for Brucella abortus, which was not present. Pregnancy varied by population (P < 0.016) but not by exposure to any agent (P > 0.213). Proportion of females lactating in autumn did not vary among populations (P > 0.247) nor by exposure to any agent (P > 0.281). Exposure did not affect productivity of elk, despite exposure levels reflective of previous surveys throughout North America and low pregnancy and calf survival in some populations. Because all surveyed elk populations showed exposure to bovine herpesvirus-1 (BHV-1), IBR would be the most likely disease to be introduced with elk, although risk is low given high seroprevalence to BHV-1 among cattle in Mexico. Conversely, brucellosis is endemic in Mexico and can significantly impact productivity of elk. Thus, contracting brucellosis from cattle is the highest disease-related threat to elk introductions or translocation in Mexico.